A randomized trial of race-related stress among African Americans with chronic kidney disease. (September 2021) - Arriola, Kimberly Jacob; Lewis, Tené T.; Pearce, Bradley; Cobb, Jason; Weldon, Brianna; Valentin, Madelyn I. Zapata; Lea, Janice; Vaccarino, Viola
Abstract: Objective: African Americans progress from early to late-stage chronic kidney disease (CKD) at a rate that is three times that of Whites. Given research that implicates social stress in poor kidney outcomes, there is a need to examine whether race-related stress contributes to these disparities. Through experimental manipulation, this study sought to determine whether acute race-related stress was associated with autonomic arousal and an inflammatory marker, which are well-established pathways to poor kidney outcomes. Further we tested the hypothesis that expectations of racism may moderate this relationship. Method: Fifty-two African American patients along the CKD continuum were randomized to recall a general or race-related stressful experience. Before, during, and after the recall, patients' blood pressure and Interleukin-6 (IL-6) were monitored. Prior to the experimental manipulation, participants completed self-reported measures of expectations of racism. Results: Across both study conditions, change in self-reported distress from baseline to stress was associated with both systolic and diastolic reactivity (both p s < .01), but not change in IL-6 responses (all p s > 0.05). A significant interaction revealed that those who were randomized to recall a race-related stressor demonstrated less diastolic blood pressure reactivity (F=4.80, p< .05) if they scored lower in expectations of racism as compared to those who scored high. Moreover, those who were randomized to the race-related stressor demonstrated greater increase in IL-6 from 45 to 90 min post-recall than those who recalled a general stressor (F=6.35, p< .05). Conclusions: Acute race-related stress may be associated with autonomic arousal and inflammatory response among African American patients along the CKD continuum, suggesting the need to further understand its role in racial disparities in CKD progression. Highlights: African Americans along the chronic kidney disease continuum were randomized to recall a race-related or general stressor. Those who recalled a race-related stressor had greater diastolic blood pressure reactivity if they generally expect racism. Expecting to experience racism was associated with greater systolic blood pressure reactivity regardless of study condition. Those who recalled a race-related stressor had greater increase in Interleukin-6 than those who recalled a general stressor.